Experimental and quantum chemical evaluation of Schiff bases of isatin as a new and green corrosion inhibitors for mild steel in 20% H2SO4 - Ansari K.R.; Quraishi M.A. (My University, 2025)
The corrosion inhibition property of Schiff bases of isatin namely 3-(4-(3-phenylallylideneamino) phenylimino)indolin-2-one (PI) and 3-(4-(4-methoxybenzylideneamino)phenylimino)indolin-2-one (MI) has studied in 20% H2SO4 for mild steel using gravimetric, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (Tafel), scanning electron microscopy (SEM) techniques and quantum chemical calculation. Inhibitors adsorption takes place by obeying Langmuir adsorption isotherm. Potentiodynamic polarization measurements showed that inhibitors acted as a mixed type but cathodically dominant. © 2015 Taiwan Institute of Chemical Engineers.